Effectiveness of Hybrid Learning in Enhancing Self-Directed Learning among University Students - Dilani Gedera; Maimunah; Wargo; Nor Azura Abdullah; Masitah Shahrill (Zabags International Journal of Education, 2025)
The digital transformation of higher education has accelerated the adoption of hybrid learning models that combine face-to-face and online instruction. This quantitative correlational study investigates the influence of hybrid learning effectiveness on university students’ self-directed learning. A sample of 120 students completed a structured Likert-type questionnaire measuring five dimensions of self-directed learning (self-regulation, intrinsic motivation, time management, initiative in seeking resources, and self-evaluation) and multiple indicators of hybrid learning effectiveness (balance of synchronous/ asynchronous activities, access to digital resources, pedagogical interactivity, and instructor support). Data were analyzed using descriptive statistics, Pearson correlation, and simple linear regression implemented in SPSS. Results indicate a positive and statistically significant relationship between hybrid learning effectiveness and students’ self-directed learning, with hybrid learning accounting for a substantial portion of variance in autonomy-related outcomes. The findings suggest that successful hybrid designs necessitate not only technological readiness but also intentional pedagogical strategies and instructor facilitation to foster learner autonomy. The study reinforces the theoretical fit of self-directed learning frameworks in hybrid contexts and offers practical guidance for institutions aiming to cultivate autonomous learners in the digital era.